A harmonized longitudinal biomarkers and cognition database for assessing the natural history of preclinical Alzheimer's disease from young adulthood and for designing prevention trials. Issue 11 (7th September 2019) - Xiong, Chengjie; Luo, Jingqin; Agboola, Folasade; Li, Yan; Albert, Marilyn; Johnson, Sterling C.; Koscik, Rebecca L.; Masters, Colin L.; Soldan, Anja; Villemagne, Victor L.; Li, Qiao‐Xin; McDade, Eric M.; et al.
Abstract: Introduction: Large longitudinal biomarkers database focusing on middle age is needed for Alzheimer's disease (AD) prevention. Methods: Data for cerebrospinal fluid analytes, molecular imaging of cerebral fibrillar β‐amyloid with positron emission tomography, magnetic resonance imaging–based brain structures, and clinical/cognitive outcomes were harmonized across eight AD biomarker studies. Statistical power was estimated. Results: The harmonized database included 7779 participants with clinical/cognitive data: 3542 were 18∼65 years at the baseline, 5865 had longitudinal cognitive data for a median of 4.7 years, 2473 participated in the cerebrospinal fluid studies (906 had longitudinal data), 2496 participated in the magnetic resonance imaging studies (1283 had longitudinal data), and 1498 participated in the positron emission tomography amyloid studies (849 had longitudinal data). The database provides adequate power for detecting early biomarker changes, and demonstrates the feasibility of AD prevention trials on middle‐aged individuals. Discussion: The harmonized database is an optimum resource to design AD prevention trials decades before symptomatic onset.